PENDAMPINGAN USAHA MAKANAN AMAN DAN SEHAT PADA IBU-IBU KEMBANG KUNING MULYO, SURABAYA - Irawati, Desrina Yusi; Widari, Nyoman Sri; Canariesa, Armadeo Ruben; Prastyo, Yohanes Okta Dwi (ABIDUMASY, 2025)
Women dominate food traders in the Kembang Kuning area. Most of the food businesses they run are small businesses carried out at home or around the grave area. The business activities carried out by Kembang Kuning Mulyo women are still relatively simple. Food products are only sold in front of the house using a table to place food. Unfortunately, traders pay little attention to hygiene standards, have limited knowledge of capital calculations and product cost, and refrain from using promotional media. The solution to overcome this problem is to provide education and practice regarding healthy and clean food business management, provide simple counseling regarding business finances, and help design promotional media such as banners or posters. Program implementation begins with problem identification, followed by implementing each activity according to plan, monitoring and evaluation, and assistance after completing the program. Through this service program, women can apply hygienic steps in every business process, calculate profits and losses from their merchandise, and have banners to beautify their stalls. Overall, this community service program ran smoothly. The partners showed high enthusiasm during the mentoring, as evidenced by their willingness to provide information, participate in counseling, and have active discussions.